The potential for developing sago-taro intercropping in South Sulawesi: a review. Issue 1 (March 2021) - Syafiuddin, M; Zubair, H; Jayadi, M; Baharuddin, B; Busthanul, N
Abstract: FAO predicts that by 2050, food production will need to increase by up to 60 percent, while at the same time there will be a scarcity of agricultural resources, especially land / land and water. Therefore, modernization of agriculture, exploiting the potential of marginal land resources and high adaptation-powered food crops such as sago ( Metroxylon sagu Rottb) is an option. However, investment in sago cultivation is seen as inefficient because it is long-term so it is not attractive, especially for poor farmers. This review is aimed at discussing the potential of developing sago plants efficiently through the introduction of Japanese taro plant, satoimo ( Colocasia esculenta var antiquorum) into sago plantations, forming the sago-taro intercropping system in South Sulawesi. It was found that the native sago vegetation area in South Sulawesi, namely in the Luwu Raya regions, was socio-economically and culturally and ecologically potential for developing sago plants. It is also known that satoimo taro has a high economic potential, and is ecologically tolerant of shade so that it can be introduced into sago plantations — up to four or five years old — to form intercropping plantations. It can be concluded that intercropping of sago-taro, both of ecologically and socio-economically and culturally has high potential to be developed in South Sulawesi, especially in the Luwu Raya regions.